Dampak Pandemi Covid-19 terhadap Pendapatan: Bukti dari Petani Pisang di Desa Bangun Harja Kecamatan Seruyan Hilir: Impact of the Covid-19 Pandemic on Income: Evidence from Banana Farmers in Bangun Harja Village, Seruyan Hilir Timur District, Seruyan Regency - Bayu Isnanto; Lili Winarti (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The Covid-19 pandemic has made it difficult for farmers to meet production costs in the future due to the delay in the distribution process of agricultural produce, and the need for agricultural commodities will indirectly impact farmers’ income. This study aims to analyze the analysis of banana farmers and the impact of the Covid-19 pandemic on the income of banana farmers in Bangun Harja Village, Seruyan downstream east sub-district. The research method uses quantitative descriptive. Data collection is carried out using questionnaires and in-depth interviews with informants. Respondents in this study were farmers who worked as a banana farmer. Determination of the sample using a simple random sampling method by giving equal rights to each member of the population. To answer the research objectives, the first is to use descriptive and the second is to use quantitative analysis with paired test analysis tools and paired sample t-test data to determine income before and after the covid-19 pandemic. The research data analysis shows that the characteristics of banana farmers include age, education, experience, land ownership, and differences in income of banana farmers before and after the COVID-19 pandemic. The average income of banana farmers before the covid-19 pandemic was Rp. 4,907,407,- per month and after the covid-19 pandemic of Rp. 3,722,222,- per month. The results of the t-test analysis also show that the significance value obtained is 0.000, which indicates a fundamental difference between the income earned by farmers before and after the covid-19 pandemic.